A prototype of e-forum for online expertise community (EfOEC) / Nur Alhana Abdul Hakim - Abdul Hakim, Nur Alhana (2005)
This project is to develop a prototype of E-Forum for Online Expertise Community. It is a web-based application using PHP technology with UML approach. The objectives of this project is to identify the procedures that needs to be followed and considered, so that the participants of the e-forum are acknowledged as an expertise or professionals by their professional's board, to define the mode of communication that will be used in e-forum so that it will be used together with the procedure that is identified and to develop a prototype of E-Forum for Online Expertise Community according to the analysis done. Methodology used in developing this application is Unified Software Development Process (USDP). It comprises of four main phases which are inception, elaboration, construction and transition. The purpose E-Forum is to record the information of users that implement this application. It's not just record or store the users information, its also generates and produce annoimcement, forum, current issues and archive which posted by them. The value change each time new user is added or deleted and data updated. Basically, E-Forum is developed in order to help the people to gain and share knowledge, skills and experiences to with each other.